A CO 2 Gas-soluble silicon nanofluid and preparation method thereof
The nanosilica is modified by grafting silane coupling agent and undergoing Michael addition reaction with polyfunctional agglomerated silicone to prepare CO2 aerosolized silicon nanofluid, which solves the high cost of existing thickeners and poor viscosity enhancement effect. The problem of this achieves efficient thickening of supercritical carbon dioxide and the reduction of the pressure of mixed CO2 with crude oil.
Patent Information
- Application Number
- CN202411814003.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-12-11
AI Technical Summary
The existing supercritical carbon dioxide thickeners cannot take into account both the cost and the viscosity-enhancing effect, and in heavy oil reservoirs, the mixed pressure of CO2 and crude oil is high, limiting the application of CO2 mixed-phase driving.
The nanosilica was modified by grafting silane coupling agent and Michael addition reaction with polyfunctional agglomerated silicone to prepare CO2 aerosolized silicon nanofluid. The nanofluid forms a network structure, which significantly improves the viscosity enhancement effect of supercritical carbon dioxide and reduces the mixing pressure between CO2 and crude oil.
It has achieved significant viscosity increase to supercritical carbon dioxide, with the highest viscosity increase ratio up to 360 times, and at the same time, the mixed phase pressure between CO2 and crude oil is reduced, and the application potential of CO2 mixed phase drive is improved.
Smart Images

Figure CN119284915B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of additives for oil and gas field development, in particular to a CO2 gas-soluble silicon nanofluid and a preparation method thereof. Background Art
[0002] At present, traditional crude oil production cannot meet the needs of economic development, and unconventional oil and gas resources are receiving more and more attention. With the exploration and development of unconventional oil and gas resources, the disadvantages of huge water resource consumption and serious environmental pollution have gradually emerged. Supercritical carbon dioxide (SC-CO2) is considered to be a very promising fracturing fluid and oil displacement agent. In addition to its characteristics of easy separation, low damage, and easy flowback, its unique oil displacement properties such as dissolution and viscosity reduction and post-pressure energy enhancement make it have great potential in unconventional oil and gas production. However, the viscosity of supercritical carbon dioxide is as low as 0.02mPa·s. This viscosity cannot carry the proppant evenly into the formation, so that the advantages of the carbon dioxide dry fracturing fluid system cannot be well utilized.
[0003] At present, supercritical dioxide thickeners are mainly hydrocarbons, siloxanes, and fluorine-containing thickeners. Among them, hydrocarbon thickeners have high dissolution pressure and often require a large amount of cosolvents; linear siloxanes have low dissolution pressure, but low viscosity increase; pure fluorine-containing thickeners have the lowest overall dissolution pressure, but the viscosity increase is the worst. For example, CN117362651A discloses a poly (uric acid ester-siloxane) polymer and a preparation method, which has a final viscosity increase of 356 times, but the preparation method uses chloroplatinic acid catalyst and hydrogen-containing siloxane, and the raw materials are expensive and the reaction stability is poor, which makes it difficult to use on site.
[0004] my country's reservoirs are mainly heavy oil. The content of polar components such as asphaltene and colloid in heavy oil is relatively high, and the viscosity is high. As a result, CO2 and crude oil systems are difficult to mix during CO2 flooding. The minimum miscibility pressure is higher than the formation fracture pressure, which greatly limits CO2 miscible flooding.
[0005] For example, CN118460196A discloses a miscibility reducing agent for reducing the minimum miscibility pressure of CO2 and crude oil and its preparation and application method. However, during the implementation process, toxic miscibility reducing agents such as benzene and white oil are still required, which limits their on-site application.
[0006] In recent years, nanomaterials have gradually attracted widespread attention due to their unique physical and chemical properties. The characteristics of nanofluids give them more excellent properties: nanoparticles are well dispersed and stable in motion, and it is not easy for particles to cluster; secondly, they have high surface activity and can be stably adsorbed on the phase interface.
[0007] For example, CN115197687A discloses a method for preparing a nanomaterial / modified acrylate-siloxane polymer supercritical carbon dioxide thickening system, which increases the original system by 30% after adding the nanomaterial, and ultimately increases by 291 times. However, the reaction is still an expensive hydrosilation reaction, and the nanomaterial is not grafted onto the polymer, which makes it impossible to apply it on a large scale.
[0008] It can be seen that the current supercritical dioxide thickener still cannot take into account both cost and viscosity-increasing effect. At the same time, the thickener can only be used as a single function, which increases the complexity of subsequent oil field development. Summary of the invention
[0009] To solve at least one of the above problems, the present invention provides a CO2 gas-soluble silicon nanofluid and a preparation method thereof.
[0010] The technical solution of the present invention is: a method for preparing CO2 gas-soluble silicon nanofluid, which comprises the following steps, calculated by mass:
[0011] Taking nano-silicon dioxide and grafting a silane coupling agent to obtain modified nano-silicon dioxide, wherein the silane coupling agent contains a group capable of undergoing a Michael addition reaction with an amino group;
[0012] Take 3-8 parts of methylsiloxane, 4-9 parts of fluorosilicone, 2-6 parts of aminosiloxane and a capping agent, and polymerize them under the action of a catalyst to obtain a multifunctional polysiloxane;
[0013] Take 1 to 3 parts of modified nano-silica and 10 parts of multifunctional polysiloxane and mix them evenly, then heat them to cause Michael addition reaction, and obtain the product after the reaction is completed.
[0014] Specifically, in the present invention, the modified nano-silicon dioxide can be prepared by using existing technologies. For example, in the prior art, toluene is used as a dispersant, the reaction temperature is 90°C, and nanoparticles and silane coupling agents are added to obtain the modified nano-silicon dioxide; in other methods, a mixed solution of acetone and water is used as a dispersant, nanoparticles and silane coupling agents are added, and ultrasonic reaction is performed to obtain the modified nano-silicon dioxide. These methods are conventional operations in the art and can be applied to the present invention.
[0015] In one embodiment of the present invention, the particle size of the nano-silicon dioxide is 10-30 nm. If the particle size of the nano-silicon dioxide is too large, it is easy to agglomerate and the performance is reduced.
[0016] In one embodiment of the present invention, the silane coupling agent is at least one of γ-methacryloxypropyltrimethoxysilane, methacryloxypropyltriethoxysilane and methacryloxypropyldimethylethoxysilane.
[0017] One embodiment of the present invention is that the preparation of modified nano-silica includes the following steps: taking 1 to 3 parts of nano-silica, adding ethanol and ultrasonically dispersing it uniformly to obtain a dispersion; taking 1 to 5 parts of a silane coupling agent, adding it to a mixture of 1 to 5% ethanol and water and dissolving it to obtain a solution; mixing the above-mentioned dispersion and ethanol-water solution, reacting for 3 to 6 hours under deoxygenation and 70 to 100° C., and after the reaction is completed, separating and purifying it to obtain a solution.
[0018] One embodiment of the present invention is that the catalyst is at least one of sodium hydroxide, potassium hydroxide, tetramethylammonium hydroxide, and potassium trimethylsilanol; and the added amount of the catalyst is 0.01-0.1% of the total mass of methylsiloxane, fluorosilicone and aminosiloxane.
[0019] One embodiment of the present invention is that the preparation of the multifunctional polysiloxane includes the following steps: taking methylsiloxane, fluorosilicone, aminosiloxane, a capping agent and a catalyst and mixing them evenly, and reacting them for 4 to 8 hours under deoxygenation and 80 to 130° C.
[0020] In one embodiment of the present invention, the methylsiloxane is at least one of octamethylcyclotetrasiloxane, dodecamethylcyclohexasiloxane, and hexadecylcyclooctasiloxane; the fluorosiloxane is at least one of 1,3,5-trimethyl-1,3,5-tris(3,3,3-trifluoropropyl)cyclotrisiloxane, (3,3,3-trifluoropropyl)trimethoxysilane, and 3,3,3-trifluoropropylmethyldimethoxysilane; and the aminosiloxane is γ-amino At least one of propyltriethoxysilane, γ-diethylenetriaminepropylmethyldimethoxysilane, and γ-aminopropylmethyldimethoxysilane; the end-capping agent is one of decamethyltetrasiloxane, octamethyldiphenyldisiloxane, tetramethyldisiloxane, heptamethyltrisiloxane, octamethyltrisiloxane, pentamethyldisiloxane, hexamethyldisiloxane, hexavinyldisiloxane or hexaphenyldisiloxane, and the amount of the end-capping agent added is 0.06-0.09 parts.
[0021] In particular, the end-capping agent is a common additive in the preparation process of polysiloxane. The greater the amount of the end-capping agent added, the lower the degree of polymerization of the polysiloxane, and vice versa. Those skilled in the art can add different amounts of the end-capping agent according to actual conditions.
[0022] One embodiment of the present invention is that the reaction temperature of the Michael addition is 100-140° C., the reaction time is 4-8 hours, and then the temperature is raised to 150-160° C. and kept warm for 1-2 hours.
[0023] In addition, the present invention also discloses a CO2 gas-soluble silicon nanofluid prepared by the above method, and the nanofluid can effectively increase the viscosity of supercritical carbon dioxide and reduce the mixed phase pressure of carbon dioxide and crude oil.
[0024] Beneficial effects: The present invention utilizes multifunctional polysiloxane grafted with γ-methacryloxypropyltrimethoxysilane to modify nano-silica to prepare gas-soluble silicon nanofluid, which forms a network structure with modified nano-silica as "cross-linking" points and polysiloxane as a chain at the microscopic level; at the macroscopic level, it has an obvious viscosity-increasing effect on supercritical carbon dioxide and a low dissolution pressure; it significantly reduces the interfacial tension between crude oil and CO2, and reduces the miscible pressure between CO2 and crude oil; the raw materials are cheap and easy to obtain, there are many selectable monomers, and the mutual solubility is good; the reaction conditions are mild and controllable, the addition of materials is convenient, and no external solvent is required; the product purification and separation is simple; and the reaction path does not have expensive catalysts or other additives. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is an infrared test result diagram of the product of Example 4;
[0026] Figure 2 This is a graph showing the one-dimensional H-NMR spectrum test results of the product FND of Example 4.
[0027] Figure 3 This is a graph showing the one-dimensional H-NMR spectrum test results of the product NPs-FND of Example 4. DETAILED DESCRIPTION
[0028] The specific implementation modes of the present invention will be described clearly and completely below in conjunction with examples and drawings. Obviously, the described examples are only some embodiments of the present invention, rather than all embodiments.
[0029] Example 1: Preparation of modified nano-silica: Add 10 g of silicon dioxide with a particle size of 25 nm to a three-necked flask, then add 1000 g of ethanol, stir and ultrasonicate at room temperature to ensure that the nano-silica is dispersed; weigh 20 g of γ-methacryloxypropyltrimethoxysilane and add it to 1000 g of an ethanol solution containing 2% deionized water, mix and hydrolyze in a beaker, cool to room temperature, and then transfer to a three-necked flask, mix thoroughly, deoxygenate with nitrogen for 30 minutes, and graft react in an oil bath at 95°C for 3.5 hours. Purify and dry to obtain modified nano-silica.
[0030] Preparation of FND (multifunctional polysiloxane): 33 g of octamethylcyclotetrasiloxane, 82 g of 1,3,5-trimethyl-1,3,5-tri(3,3,3-trifluoropropyl)cyclotrisiloxane, 25 g of γ-aminopropylmethyldiethoxysilane, 0.804 g of hexamethyldisiloxane and 0.0447 g of tetramethylammonium hydroxide were added into a three-necked bottle, and the ring-opening reaction was carried out in an oil bath at 85°C for 7.5 h, and the temperature was lowered to obtain FND.
[0031] Preparation of NPs-FND (CO2 gas-soluble silicon nanofluid): Add 10 g of vinyl-terminated nano-silica and 100 g of FND into a three-necked bottle, seal and stir, pass nitrogen to deoxygenate for 30 minutes, carry out grafting reaction in an oil bath at 135°C for 4.5 hours, then keep warm at 150°C for 2 hours to purify and obtain NPs-FND.
[0032] Example 2: Preparation of modified nano-silica: Add 20 g of silicon dioxide with a particle size of 15 nm to a three-necked flask, then add 1000 g of ethanol, stir and ultrasonicate at room temperature to ensure that the nano-silica is dispersed; weigh 40 g of γ-methacryloxypropyltrimethoxysilane and add it to 1000 g of ethanol solution containing 4% deionized water, mix and hydrolyze in a beaker, cool to room temperature, transfer to a three-necked flask, mix thoroughly, deoxygenate with nitrogen for 30 minutes, graft react in an oil bath at 75°C for 5.5 hours, purify and dry to obtain modified nano-silica.
[0033] Preparation of FND: In a 250 mL three-necked bottle, 37 g of octamethylcyclotetrasiloxane, 46 g of 1,3,5-trimethyl-1,3,5-tri(3,3,3-trifluoropropyl)cyclotrisiloxane, 40 g of γ-aminopropylmethyldiethoxysilane, 0.653 g of hexamethyldisiloxane, and 0.086 g of tetramethylammonium hydroxide were added, and the ring-opening reaction was carried out in an oil bath at 105 ° C for 5.5 h, and the temperature was lowered to obtain FND.
[0034] Preparation of NPs-FND: Add 20 g of modified nano-silica and 100 g of FND into a three-necked bottle, seal and stir, pass nitrogen to deoxygenate for 30 min, carry out grafting reaction in an oil bath at 110° C. for 6.5 h, then keep warm at 150° C. for 1 hour to purify and obtain NPs-FND.
[0035] Example 3: Preparation of modified nano-silica: Add 15 g of silicon dioxide with a particle size of 25 nm to a three-necked flask, then add 1000 g of ethanol, stir and ultrasonicate at room temperature to ensure that the nano-silica is dispersed; weigh 15 g of γ-methacryloxypropyltrimethoxysilane and add it to 500 g of ethanol solution containing 3% deionized water, mix and hydrolyze in a beaker, cool to room temperature, and then transfer to a three-necked flask. After fully mixing, deoxygenate with nitrogen for 30 minutes, graft react in an oil bath at 85°C for 4.5 hours, purify and dry to obtain modified nano-silica.
[0036] Preparation of FND: Add 74 g of octamethylcyclotetrasiloxane, 46 g of 1,3,5-trimethyl-1,3,5-tri(3,3,3-trifluoropropyl)cyclotrisiloxane, 30 g of γ-aminopropylmethyldiethoxysilane, 0.761 g of hexamethyldisiloxane, and 0.075 g of tetramethylammonium hydroxide into a three-necked bottle, and carry out grafting reaction in an oil bath at 115° C. for 4.5 h. After cooling, FND is obtained.
[0037] Preparation of NPs-FND: Add 15 g of modified nano-silica and 100 g of FND into a three-necked bottle, seal and stir, pass nitrogen to deoxygenate for 30 min, carry out grafting reaction in an oil bath at 120°C for 5.5 h, then keep warm at 160°C for 1 hour to purify and obtain NPs-FND.
[0038] Example 4: Preparation of modified nano-silica: Add 25 g of silicon dioxide with a particle size of 15 nm to a three-necked flask, then add 1000 g of ethanol, stir and ultrasonicate at room temperature to ensure that the nano-silica is dispersed; weigh 45 g of γ-methacryloxypropyltrimethoxysilane and add it to 1000 g of ethanol solution containing 5% deionized water, mix and hydrolyze in a beaker, cool to room temperature, and then transfer to a three-necked flask. After fully mixing, deoxygenate with nitrogen for 30 minutes, graft react in an oil bath at 85°C for 4.5 hours, purify and dry to obtain modified nano-silica.
[0039] Preparation of FND: Add 74 g of octamethylcyclotetrasiloxane, 46 g of 1,3,5-trimethyl-1,3,5-tri(3,3,3-trifluoropropyl)cyclotrisiloxane, 55 g of γ-aminopropylmethyldiethoxysilane, 0.8532 g of hexamethyldisiloxane, and 0.153 g of tetramethylammonium hydroxide into a three-necked bottle, and carry out grafting reaction in an oil bath at 125° C. for 4 h. After cooling, FND is obtained.
[0040] Preparation of NPs-FND: Add 25 g of modified nano-silica and 100 g of FND into a three-necked bottle, seal and stir, pass nitrogen to deoxygenate for 30 min, carry out grafting reaction in an oil bath at 105°C for 7.5 h, then keep warm at 150°C for 2 h to purify and obtain NPs-FND.
[0041] Comparative Example 1
[0042] In a three-necked flask, 74 g of octamethylcyclotetrasiloxane, 46 g of 1,3,5-trimethyl-1,3,5-tri(3,3,3-trifluoropropyl)cyclotrisiloxane, 38 g of γ-aminopropylmethyldiethoxysilane, 0.828 g of hexamethyldisiloxane and 0.0258 g of tetramethylammonium hydroxide were added. The mixture was subjected to a ring-opening reaction at 100 ° C in an oil bath for 6 h, then kept at 160 ° C for 1 hour, and FND was obtained after cooling.
[0043] Comparative Example 2
[0044] In a three-necked flask, 74 g of octamethylcyclotetrasiloxane, 46 g of 1,3,5-trimethyl-1,3,5-tri(3,3,3-trifluoropropyl)cyclotrisiloxane, 38 g of γ-aminopropylmethyldiethoxysilane, 0.828 g of hexamethyldisiloxane and 0.0258 g of tetramethylammonium hydroxide were added. The reaction was carried out in an oil bath at 120 ° C for 4 h, then kept at 150 ° C for 2 hours, and FND was obtained after cooling.
[0045] Preparation of NPs / FND: 20 g of 20 nm unmodified nano-silica and 100 g of FND were added to a three-necked bottle, sealed and stirred, nitrogen was passed to deoxygenate for 30 min, and kept in an oil bath at 100° C. for 6 h to obtain NPs / FND.
[0046] In order to further illustrate the specific performance of the product obtained in the embodiment of the present invention, it is tested below.
[0047] 1. Characterization
[0048] The FND and NPs-FND of Example 4 were subjected to infrared testing, and the final results were as follows: Figure 1 As shown, Figure 1 The a line in the figure represents the infrared test result of FND. Figure 1 Line b in the figure shows the infrared test results of NPs-FND.
[0049] like Figure 1 As shown by line a, 3350cm -1 1597cm -1 The absorption peaks at 2960cm are the stretching and deformation vibration peaks of -NH2; -1 The peak at 1408cm is the stretching vibration absorption peak of C-H in -CH3; -1 It is the deformation vibration absorption peak of -CH3; 1368cm -1 Absorption peak of -CH2CH2CF3; 1315cm -1 The absorption peak of CH2-CH2 is at 1260cm -1 The peak at 1210cm is the deformation vibration absorption peak of Si-CH3; -1 Absorption peaks of CF3: 960, 898 cm -1 The absorption peaks at 1058 and 1023 cm are the stretching vibration peaks of C-C. -1 The absorption peaks at 1260, 865, 803 cm are the stretching vibration peaks of Si—O—Si; -1 The characteristic absorption peak of Si-C is at , and the infrared results show that the fluorinated methylsiloxane polymer is successful.
[0050] like Figure 1As shown in the middle line b, the absorption peak of -NH2 disappears and the absorption peak of the carbonyl group in γ-methacryloxypropyltrimethoxysilane appears. The infrared results show that the modification of nano-silica grafted with fluorinated polysiloxane is successful.
[0051] The FND and NPs-FND obtained in Example 4 were subjected to one-dimensional H-NMR spectrum testing. The final results are as follows: Figure 2 , Figure 3 shown.
[0052] from Figure 2 It can be seen that the large peak at 0.04ppm is attributed to the proton associated with the methyl group connected to the atom; 0.51ppm represents the proton of the terminal CH3-Si; the peaks at 2.57, 1.48 and 1.07ppm represent the propyl structure; the peak at 1.07ppm represents the amino group; and the peak at 2.03ppm represents the proton peak of -CH2 directly connected to -CF3.
[0053] from Figure 3 It can be seen that the protons at 1.18, 3.38, 3.78 ppm and the like represent the protons related to the methyl, methylene and methine groups on the γ-methacryloxypropyltrimethoxysilane part, indicating that the modification of nano-silica grafted with fluorinated polysiloxane is successful.
[0054] 2. Thickening performance
[0055] Take the NPs-FND of Examples 1 to 4, the FND of Comparative Example 1, and the NPs / FND of Comparative Example 2, and add them into a high-temperature and high-pressure visual dissolution kettle in an amount of 3 wt %, set the kettle temperature to 40 ° C, inject carbon dioxide until the system pressure reaches 10 MPa, start stirring, and after the fluid in the kettle is stable, use a PAC rotational viscometer to test its viscosity, and compare it with pure supercritical carbon dioxide to obtain the viscosity increase multiple, wherein the shear rate is 170 s -1 The final measured viscosity increasing effect is shown in Table 1.
[0056] Table 1 Thickening multiples of NPs-FND, FND and NPs / FND for supercritical carbon dioxide
[0057] Sample No. Viscosity ratio (times) NPs-FND of Example 1 260 NPs-FND of Example 2 315 NPs-FND of Example 3 305 NPs-FND of Example 4 360 FND of Comparative Example 1 157 NPs / FND of Comparative Example 2 198
[0058] It can be seen from Table 1 that the silicon nanofluid prepared in the embodiment of the present invention has a good viscosity increasing effect, which can be up to 360 times.
[0059] 3. Miscible pressure
[0060] The relationship curve between pressure and interfacial tension was obtained using a high-temperature and high-pressure interfacial tension meter. The experimentally measured oil-gas interfacial tension and pressure are linearly related. The pressure at which the interfacial tension is 0 after linear extrapolation is the minimum miscibility pressure of crude oil after adding the miscibility reducer measured by the interfacial tension method.
[0061] At a temperature of 80°C, the minimum miscible pressure between pure CO2 and the crude oil was first measured using a high temperature and high pressure interfacial tension meter. 3.0% of the products of Examples 1-4 and Comparative Examples 1-2 were taken and shaken evenly with the dehydrated crude oil, placed in an 80°C constant temperature box, left for more than 12 hours, and the minimum miscible pressure was measured using a high temperature and high pressure interfacial tension meter. The final results are shown in Table 2.
[0062] Table 2 Reduction of the miscibility pressure of CO2 and crude oil by NPs-FND, FND and NPs / FND
[0063] Sample No. Reduction NPs-FND of Example 1 9.8% NPs-FND of Example 2 11.5% NPs-FND of Example 3 10.4% NPs-FND of Example 4 12.6% FND of Comparative Example 1 8.2% NPs / FND of Comparative Example 2 9.6%
[0064] It can be seen from Table 2 that the silicon nanofluid prepared in the embodiment of the present invention can significantly reduce the miscible pressure of carbon dioxide and crude oil, which can be reduced by up to 12.6%.
[0065] In summary, the silicon nanofluid prepared in the embodiment of the present invention can thicken supercritical carbon dioxide and significantly reduce the mixed phase pressure of carbon dioxide and crude oil. It can be used for multiple purposes with one dose and has high application value.
[0066] The above description is only a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Although the present invention has been disclosed as a preferred embodiment as above, it is not intended to limit the present invention. Any technician familiar with the profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A method for preparing CO2 gas-soluble silicon nanofluid, characterized in that: The method comprises the following steps, in parts by mass: Taking nano-silicon dioxide and grafting a silane coupling agent to obtain modified nano-silicon dioxide, wherein the silane coupling agent contains a group capable of undergoing a Michael addition reaction with an amino group; 3-8 parts of methylsiloxane, 4-9 parts of fluorosilicone, 2-6 parts of aminosiloxane and a capping agent are polymerized under the action of a catalyst to obtain a multifunctional polysiloxane; the catalyst is at least one of sodium hydroxide, potassium hydroxide, tetramethylammonium hydroxide and potassium trimethylsilanol; the amount of the catalyst added is 0.01-0.1% of the total mass of the methylsiloxane, fluorosilicone and aminosiloxane; Take 1 to 3 parts of modified nano-silica and 10 parts of multifunctional polysiloxane and mix them evenly, then heat them to cause Michael addition reaction, and obtain the product after the reaction is completed.
2. The method according to claim 1, characterized in that The particle size of the nano silicon dioxide is 10-30 nm.
3. The method according to claim 1, characterized in that The silane coupling agent is at least one of γ-methacryloxypropyl trimethoxysilane, methacryloxypropyl triethoxysilane and methacryloxypropyl dimethylethoxysilane.
4. The method according to claim 1, characterized in that: The preparation of modified nano-silica includes the following steps: taking 1 to 3 parts of nano-silica, adding ethanol and ultrasonically dispersing it uniformly to obtain a dispersion; taking 1 to 5 parts of a silane coupling agent, adding it to a mixture of 1 to 5% ethanol and water and dissolving it to obtain a solution; mixing the above dispersion and ethanol-water solution, reacting for 3 to 6 hours under deoxygenation and 70 to 100° C., and after the reaction is completed, separating and purifying it to obtain the obtained product.
5. The method according to claim 1, characterized in that The preparation of the multifunctional polysiloxane comprises the following steps: taking methylsiloxane, fluorosilicone, aminosiloxane, a capping agent and a catalyst and mixing them evenly, and reacting them for 4 to 8 hours under the conditions of deoxygenation and 80 to 130° C. to obtain the polysiloxane.
6. The method according to claim 1, characterized in that The methylsiloxane is at least one of octamethylcyclotetrasiloxane, dodecamethylcyclohexasiloxane, and hexadecylcyclooctasiloxane; the fluorosiloxane is at least one of 1,3,5-trimethyl-1,3,5-tri(3,3,3-trifluoropropyl)cyclotrisiloxane, (3,3,3-trifluoropropyl)trimethoxysilane, and 3,3,3-trifluoropropylmethyldimethoxysilane; the aminosiloxane is γ-aminopropyltriethoxysilane. The end-capping agent is one of decamethyltetrasiloxane, octamethyldiphenyldisiloxane, tetramethyldisiloxane, heptamethyltrisiloxane, octamethyltrisiloxane, pentamethyldisiloxane, hexamethyldisiloxane, hexavinyldisiloxane or hexaphenyldisiloxane, and the amount of the end-capping agent is 0.06-0.09 parts.
7. The method according to claim 1, characterized in that The reaction temperature of the Michael addition is 100-140° C., the reaction time is 4-8 hours, and then the temperature is raised to 150-160° C. and kept warm for 1-2 hours.
8. A CO2 gas-soluble silicon nanofluid, prepared by the method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Poly (urea-siloxane) polymer as well as preparation method and application thereof
CN117362651A
Mixture reducer for reducing minimum miscible pressure of CO2 and crude oil and preparation and application methods thereof
CN118460196A
Preparation method and application of nanometer material / modified acrylate-siloxane polymer supercritical carbon dioxide thickening system
CN115197687A